Duration of ruptured membranes and mother‐to‐child HIV transmission: a prospective population‐based surveillance study. (22nd May 2015) - Peters, H; Byrne, L; De Ruiter, A; Francis, K; Harding, K; Taylor, GP; Tookey, PA; Townsend, CL
Abstract : Objective: To investigate the association between duration of rupture of membranes (ROM) and mother‐to‐child HIV transmission (MTCT) rates in the era of combination antiretroviral therapy (cART). Design: The National Study of HIV in Pregnancy and Childhood (NSHPC) undertakes comprehensive population‐based surveillance of HIV in pregnant women and children. Setting: UK and Ireland. Population: A cohort of 2398 singleton pregnancies delivered vaginally, or by emergency caesarean section, in women on cART in pregnancy during the period 2007–2012 with information on duration of ROM; HIV infection status was available for 1898 infants. Methods: Descriptive analysis of NSHPC data. Main outcome measures: Rates of MTCT. Results: In 2116 pregnancies delivered at term, the median duration of ROM was 3 hours 30 minutes (interquartile range, IQR 1–8 hours). The overall MTCT rate for women delivering at term with duration of ROM ≥4 hours was 0.64% compared with 0.34% for ROM <4 hours, with no significant difference between the groups (OR 1.90, 95% CI 0.45–7.97). In women delivering at term with a viral load of <50 copies/ml, there was no evidence of a difference in MTCT rates with duration of ROM ≥4 hours, compared with <4 hours (0.14% for ≥4 hours versus 0.12% for <4 hour; OR 1.14, 95% CI 0.07–18.27). Among infants born preterm with infection status available, there were no transmissions in 163 deliveries where the maternal viral load was <50 copies/ml. Conclusions: No association was found between duration of ROM and MTCT in women taking cART. Tweetable abstract: Rupture of membranes of more than 4 hours is not associated with MTCT of HIV in women on effective ART delivering at term. Tweetable abstract: Rupture of membranes of more than 4 hours is not associated with MTCT of HIV in women on effective ART delivering at term.